Defying expectations: factors influencing MBA graduates' entrepreneurial intentions - Nicolas A. Nunez; Giuliana Cornejo-Meza; Rafael Fernández-Concha (Cogent Business & Management)
This study examines the factors shaping entrepreneurial intentions among MBA graduates in Peru, an emerging economy where entrepreneurship is crucial for economic growth. Using Ajzen’s Theory of Planned Behavior (TPB) as a framework, a survey of 444 MBA graduates assessed the influence of entrepreneurial self‑efficacy, locus of control, subjective norms, environmental support, and attitude towards entrepreneurship. Findings from structural equation modeling (PLS‑SEM) reveal that entrepreneurial self‑efficacy and locus of control exert the strongest positive effects on entrepreneurial intentions. However, subjective norms and environmental support show weak or even negative influences, challenging conventional assumptions. Surprisingly, attitude towards entrepreneurship, while statistically significant, has a practically negligible negative effect. This study enriches the understanding of how entrepreneurship education shapes entrepreneurial intentions in developing economies, emphasizing the intricate interactions between psychological, social, and contextual factors. It refines the application of TPB in such contexts and fills gaps in existing literature. The findings suggest that MBA programs should focus on strengthening entrepreneurial self‑efficacy and locus of control while addressing other key determinants. Policymakers and educators should implement experiential learning and targeted interventions to enhance entrepreneurial mindsets among highly educated individuals in emerging markets.